'The Danger is Two-Fold': Decolonisation and Cold War in Anti-Communist Asia, 1955–7. Issue 2 (15th March 2017) - Kraus, Charles
ABSTRACT: This article examines the intersection between the Cold War and decolonisation in anti-Communist Asia in the 1950s. Drawing on the papers of former South Korean President Syngman Rhee housed at Yonsei University, the article explores both the motivations behind as well as the constraints upon South Korea's efforts to cultivate a military alliance in what it called 'Free Asia'. Articulating some of the concrete political differences between South Korea and its potential partners in Asia, the article argues that Rhee's hardline views of the Cold War were interwoven with his ambivalence about Japan's reintegration in the post-war world. As a result of this intersection between the Cold War and decolonisation, the South Korean President was unable to achieve consensus with the rest of anti-Communist Asia. In exploring this chapter of South Korean diplomacy, the article calls on Cold War diplomatic history to integrate non-Communist Asia and for the historiography of decolonisation to investigate the legacies of Japan's empire in post-war Asia. It also suggests that scholars ought to reflect more deeply on the interrelationship between the Cold War and decolonisation.